The Cape Town International Convention Centre from the inside: The family physicians' view of the 'Hospital of Hope' - Steve Reid; Tasleem Ras; Klaus von Pressentin (AOSIS, 2020)
This short report captures the week-by-week reflections of a group of family physicians who joined the clinical and operational management teams tasked with providing the in-patient service of an 862-bed COVID-19 field hospital. The 'Hospital of Hope' at the Cape Town International Convention Centre (CTICC) was established as an intermediate care facility specifically to cope with the effects of the COVID-19 pandemic in Cape Town metropole. In an extraordinary feat of engineering, the conference centre floor was transformed within a matter of weeks into wards with piped oxygen at each bed. Whilst the emergency medicine specialists took the lead in designing and commissioning the facility, the medical management and staff were drawn mostly from family physicians. This report is a short reflection on the experience of the first 4 weeks of managing patients in this repurposed space. Our insights evolved during various formal and informal learning conversations as the in-patient service became more organised over time. We hope that these insights, as well as the process of reaching them, will assist other colleagues in serving their communities during this difficult moment in history; moreover, it may reflect a renewed appreciation for team-based interdisciplinary efforts in achieving person-centred care.